2017
DOI: 10.21037/jtd.2017.02.82
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial embolization of intralobar pulmonary sequestration in a young adult with hemoptysis

Abstract: Intralobar pulmonary sequestration is a rare congenital malformation characterized by the presence of dysplastic lung that does not communicate with the tracheobronchial tree, and has aberrant systemic arterial supply. While most are asymptomatic, they rarely can present with hemoptysis, which has been traditionally managed with surgical resection of the sequestration. We report a case of an 18-year-old male who presented with acute large-volume hemoptysis on a background of recurrent minor episodes of hemopty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 23 publications
0
34
0
3
Order By: Relevance
“…Furthermore, very few studies have compared the results of embolization and surgical resection and reported which treatment is better in adult patients . Some authors believe that embolization can occlude the arterial supply, leading to sequestration infarction, and thus is an alternative treatment method to conventional surgical resection . As such, embolization is thought by some to be superior to surgery as it minimizes complications and shortens hospital stay …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, very few studies have compared the results of embolization and surgical resection and reported which treatment is better in adult patients . Some authors believe that embolization can occlude the arterial supply, leading to sequestration infarction, and thus is an alternative treatment method to conventional surgical resection . As such, embolization is thought by some to be superior to surgery as it minimizes complications and shortens hospital stay …”
Section: Discussionmentioning
confidence: 99%
“…12 Some authors believe that embolization can occlude the arterial supply, leading to sequestration infarction, and thus is an alternative treatment method to conventional surgical resection. 10 As such, embolization is thought by some to be superior to surgery as it minimizes complications and shortens hospital stay. 13 An adverse effect of embolization is the distant migration of embolization products resulting in the embolization of non-targeted arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pulmonary bleeding is still one of the most pressing problems in surgery. Pulmonary bleeding is the most dangerous complication of a number of diseases [1,2]. There are 40 nosological forms that can be complicated by pulmonary hemorrhage (PH); some authors describe PH as a complication in more than 100 diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To date, X-ray vascular occlusion (REO) of the bronchial arteries allows patients to avoid surgery at the height of bleeding. Despite the fact that this method has been used in clinical practice for more than 30 years, the questions concerning the tactics of interventions and the choice of embolizing materials [14,15]. Efficiency of the method in the long-term period is devoted to the publications.…”
Section: Introductionmentioning
confidence: 99%
“…In cases with severe infected ILS, segmentectomy or ligation of the aberrant artery is insufficient with a favour for lobectomy to avoid contamination . In cases of ILS with arteriovenous shunting and heart failure, endovascular embolization is a viable alternative to surgery, while the surgical resection is a preferred strategy for cases with recurrent chest infection …”
mentioning
confidence: 99%